Impact of PETLLEP-based mental imagery on nursing and midwifery students’ skill of nasogastric tube insertion and self-efficacy - AZAM SAEIDIKIA; S.A. VAGHARSEYYEDIN; ZAHRA DANAIE; SHAHNAZ TABIEI (International Journal of Psychosocial Rehabilitation, 2020)
Background and Aim: Effective learning of practical and clinical skills is one of the top priorities for nursing and midwifery students. Therefore, the most efficient method(s) for teaching skills should be adopted to maximize student learning. This study aimed to determine the effect of mental imagery practice based on the PETTLEP model on the self-efficacy and skill of nursing and midwifery students in nasogastric tube insertion. Methods: A randomized controlled field trial was conducted with 68 nursing and midwifery students at Birjand University of Medical Sciences (BUMS). At baseline, the participants completed a demographics form, the Revised Movement Imagery Questionnaire (MIQ-R), the Learning Self-Efficacy Scale (L-SES), and a checklist of nasogastric tube insertion skills. Subsequently, the students were randomly assigned to an experimental group and a control group. During a 90-minute session, the researcher taught the mental imagery technique for nasogastric tube insertion to the experimental group based on the PETTLEP model. The experimental group practiced mental imagery for nasogastric tube insertion three times a week for four weeks at the clinical skills lab located in (BUMS). During this time, the control group performed the usual nasogastric tube insertion practice. When the training sessions were finished for all students, the self-efficacy questionnaire and nasogastric tube insertion checklist were completed again. Results: Statistical analysis showed that the frequency distribution of gender and interest in the nursing field had a significant difference between students in experimental and control groups (p <0.05). After adjustment, the covariance analysis showed that the self-efficacy and its mean difference scores were not significantly different between the groups before and after the intervention (p> 0.05). However, after adjustment, the mean post intervention scores of nasogastric tube insertion skill and its mean difference were significantly higher in the experimental group than the control group (p <0.05). Conclusion: The PETTLEP-based mental imagery practice contributes to the development of nasogastric tube insertion skills in students. Therefore, the application of this method is suggested for teaching the skills considered in the Fundamentals of nursing course of nursing and midwifery students.